Arlen Specter : Scandals, Conspiracies, and Crisis in Focus - Laine, Evan Edward (Book collections on Project MUSE., 2021)
"From his early work as a lawyer on the Warren Commission investigating the assassination of President John F. Kennedy to his days as Philadelphia's district attorney to his thirty-year career as a United States Senator from Pennsylvania, Arlen Specter found himself consistently in the middle of major historical events. During his five terms as senator, Spector met with the likes of Palestine Liberation Organization leader Yasser Arafat and Cuban Prime Minister Fidel Castro and made significant contributions during the fallout of both the Iran-Contra scandal and the Clinton impeachment. His work had a profound influence on the configuration of the United States Supreme Court, the criminal justice system, LGBTQ rights, and stem cell research. Photographs from Specter's personal collection highlight many of these key moments, revealing the rich narrative not only of one man's political career, but how it helped shape a nation. While it will probably be long debated whether Specter's complex and controversial political legacy merits mainly praise or criticism, Arlen Specter sheds new light on the life of a man who fought to make a difference"--